Flowering and fruit set in vanilla (Vanilla planifolia Andr.) - UMESHA, Y G SHADAKSHARI, H M CHANDRAPPA, K (Journal of Spices and Aromatic Crops, 1996)
Cultivation of vanilla (Vanilla planifolia Andr.) is becoming increasingly popular in recent years in the hill zone of Karnataka, India.